Exit strategies, capital flight and speculative attacks: Europe's version of the trilemma - Andreas Steiner; Sven Steinkamp; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2017)
In the winter 2011/12 a wave of internal capital .ight prompted the ECB to abandon its exit strategy and to announce an unprecedented monetary expansion. We analyze this episode in several dimensions: (i) by providing an event-study analysis covering key variables from national central banks.balance sheets, (ii) by rationalizing their patterns in a portfolio balance model of the exchange rate, augmented by institutional characteristics of the TARGET2 system, and (iii) by proposing a theory-based index of exchange market pressure within the euro area. We argue that the euro area entails an inherent policy trilemma that makes it prone to speculative attacks.
Keywords: E42; F36; F41; F45; 330; Currency Union; Exchange Market Pressure; Policy Trilemma; Speculative Attack; TARGET2